THE ROLE OF ZAKAT IN REDUCING POVERTY AND IMPROVING COMMUNITY WELFARE - Alfina Fitriani; Dewi Sekar Wahyuningsih; Luthfi Muzakky; Yuni Suparni, (International Journal of Economics Education Research (IJEER), 2025)
Muslims are required to set aside part of their income for zakat, which is donated to the underprivileged. One of the instruments of Islamic economics, zakat, has enormous potential to drive social and economic progress. The purpose of this study is to examine how zakat functions in the Indonesian economy, especially as a means to combat poverty and improve people's financial well-being. To analyze various literatures from various sources, this study combines qualitative methods with literature review methodology. By using the literature study method, this study found that productive zakat has a significant impact on reducing poverty levels and improving people's economic well-being. In addition to being a form of worship, zakat also functions as a fair and sustainable redistribution of wealth, which if managed properly, can be an important element in Islamic fiscal policy and a strategy for national economic development. In conclusion, by reducing poverty, zakat plays an important role in building a more just and sustainable society. To maximize the potential of zakat in achieving the goal of reducing poverty in society, it is important to manage it properly and transparently.